Common hippopotamus in Nigeria: New census data and literature review confirm the conservation importance of sites outside protected areas. Issue 10 (3rd August 2020) - Baker, Lynne R.; Che, Jennifer; Teneke, Vastinah N.; Kadala, Edward; Uba, Mikailu S.; Geoffrey, Nachamanda; Haskainu, Calvin
Abstract: Once abundant across Africa, the common hippopotamus is threatened owing to habitat degradation and loss, hunting, and negative human–wildlife interactions. West African populations are notably small and fragmented and therefore at greatest risk. In Nigeria, Africa's most populous nation, the IUCN estimates that only 100 hippos remain. They occur in protected areas, such as national parks and game reserves, and outside protected areas in estuarine habitats, inland rivers, lakes, and reservoirs. However, the status of hippos in most sites is poorly known. Reliable data are needed to better ascertain the status of this species in Nigeria. Over five days in December 2018 and May 2019, motorized boats were used to conduct a census of the hippo population in Kiri Dam reservoir, a large‐dam reservoir along the Gongola River, a major tributary of the Benue River, in north‐eastern Nigeria. These findings were compared with data on hippo abundance from several sites across Nigeria and the Benue River basin in North Cameroon. A minimum of 56 hippos (51 adults and 5 calves) were recorded, predominantly in the transitional zone of the reservoir. Based on available data, hippos in Kiri reservoir currently represent the largest recorded population in Nigeria, exceeding individual populations in official protected areas. Research and conservation efforts for hippos in Nigeria should focus on assessing their status and improving protection in key sites and increasing connectivity among populations. Special attention should be paid to populations within the Benue River basin, which is emerging as critical for hippopotamus conservation in west‐central Africa.